2020
DOI: 10.3389/fpsyt.2020.00461
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Morphological Background in Selected Functional and Inflammatory Gastrointestinal Diseases in fMRI

Abstract: The study focuses on evaluation of the Default Mode Network (DMN) activity in functional magnetic resonance imaging (fMRI) in resting state in patients with functional dyspepsia (FD) and irritable bowel syndrome (IBS), Crohn's disease and colitis ulcerosa (IBD) in comparison to healthy volunteers. We assume that etiology of both functional and nonspecific inflammatory bowel diseases is correlated with disrupted structure of axonal connections. We would like to identify the network of neuronal connections respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Both abnormalities of SMA and the cerebellum may be involved in the pathophysiology of patients with MDD. In addition, increased connectivity was observed in the left SMA in patients with functional gastroenterological diseases compared with HCs, which was interpreted as “the GI symptoms might be reactions to auditory and imaginary stimuli” ( 31 ), because the SMA was reported to support a flexible participation in the sensorimotor processes to enable auditory and imaginary perception ( 73 ). Conformably, higher ReHo in the bilateral SMA was observed in MDD patients with GI symptoms than that in HCs in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both abnormalities of SMA and the cerebellum may be involved in the pathophysiology of patients with MDD. In addition, increased connectivity was observed in the left SMA in patients with functional gastroenterological diseases compared with HCs, which was interpreted as “the GI symptoms might be reactions to auditory and imaginary stimuli” ( 31 ), because the SMA was reported to support a flexible participation in the sensorimotor processes to enable auditory and imaginary perception ( 73 ). Conformably, higher ReHo in the bilateral SMA was observed in MDD patients with GI symptoms than that in HCs in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have reported that patients with MDD have brain structural (21)(22)(23) or functional (24)(25)(26)(27) changes. Moreover, other studies have observed abnormal structural and functional brain MRI data in digestive system diseases, like irritable bowel syndrome (IBS) (28,29), other functional bowel disorders (30), and inflammatory gastrointestinal diseases (31). A few scientists have tried to examine whether MDD patients with GI symptoms had brain imaging changes and a previous study reported that MDD patients with GI symptoms showed significantly lower gray matter volume (GMV) and regional homogeneity (ReHo) in the left middle frontal gyrus, precentral gyrus, right superior frontal gyrus, and the middle frontal gyrus, as well as higher ReHo in the left superior temporal gyrus, compared to MDD patients without GI symptoms (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the connectome of the VSM, a region of interest including the dorsal motor nucleus of the vagus, presented several strong connections with the cortex (cingulate and insular cortex, pericallosal sulcus), thalamus, cerebellum, basal ganglia, as well as with brainstem nuclei, such as the VTA-PBP, IC and PnO-PnC. In addition, gastrointestinal disease has an impact on the connectivity of the default mode network with other brain regions [Skrobisz et al, 2020]. Ascending viscera-sensory pathways through the vagal nerve enter the solitary nucleus (part of VSM) and are further relayed to the parabrachial nuclei, raphe nuclei, locus coeruleus and to the forebrain, which crucially are present in our connectome.…”
Section: Sources Of Resting State Fmri Signal Fluctuationsmentioning
confidence: 99%
“…Structural ( Bell-McGinty et al, 2002 ; Depping et al, 2016 ; Hyett et al, 2018 ) and functional ( Bluhm et al, 2009 ; Guo et al, 2013b , Chen et al, 2015 ; Guo et al, 2018a ) brain changes have already been reported in many previous studies of MDD. Meanwhile, some previous studies have reported structural and functional brain image changes in digestive system diseases ( Kwan et al, 2005 ; Song et al, 2006 ; Blankstein et al, 2010 ; Skrobisz et al, 2020 ). Thus, some researchers tried to study whether MDD patients with GI symptoms exhibited abnormal brain imaging data and observed altered gray matter volume (GMV) and regional homogeneity (ReHo) ( Yan et al, 2019 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%